The Al Jazeera phenomenon : critical perspectives on new Arab media - Zayani, Mohamed, 1965- (London : pluto press, 2005)
Edited by Mohamed Zayani, this collection of essays provides an insight into, and critical analysis of, a media phenomenon that persists in defying understanding. The book sheds light on various aspects of the network, including its politics, coverage of regional crises, and its treatment of the West